ANALYSIS OF MORAL VALUES IN “GIE” FILM BY RIRI RIZA - Ummu Humaira; Taib Latif; Hujaefa Hi. Muhammad (Universitas Khairun, 2023)
This study aims to determine the moral values contained in the film Gie by Riri Riza. The theory used in this thesis is Lickona's theory. This study applied descriptive qualitative methods to explain and describe every moral value contained in the film. The subject of this research is the film Gie by Riri Riza. In conducting this study, researchers used documentary techniques to collect data from reading the synopsis of the film and watching the film “Gie”. There are seven types of moral values found in the film: responsibility, respect, wisdom, democracy, self-discipline, courage and supports. The most dominant moral value in this film is wisdom.